Life Cycle Assessment of Residential Buildings Construction (Case Study: Tehran) - Mohsen Adaei Khezri; Hamidreza Kamalan (Environmental Energy and Economic Research)
The construction industry, currently, is encountered with several issues such as lack of proper supervision and generating and accumulating a lot of debris. Considering the building as a part of nature and an inanimate creature, it interacts with the natural ecosystem and contributes to the cycle of life. In this regard, building materials should be selected in coordination with the surrounding environment and impose the least negative impact on the natural environment. The current research has been done to apply Life Cycle Assessment (LCA) approach on residential buildings construction and assess the impacts of building material, solely and altogether, on the environment. For this purpose, IMPACT 2002+ method utilizing SimaPro software has been applied to evaluate the processes and materials used for construction of a six-floor concrete structure building in Tehran. The results indicate that among the construction materials, stone production with the single score of 64 and steel production with the single score of 27 have the highest environmental impacts. Besides, a LCA has been done for comparing environmental impacts of the steel structure buildings versus the concrete ones, resulting in an inferior level for steel buildings.